Entre o lacón con grelos e o festival do cabrito: usos da memória e novas funcionalidades nos entroidos galegos - Godinho, Paula (Trabalhos de Antropologia e Etnologia, 2020)
The purpose of this text is to question the changes in food consumption in Vilariño de Conso, Galicia, at a significant moment of the annual cycle: the carnival. My argument is based on the need to place the current ethnography into an extended long-time cycle: rural long time, post-civil war, disarticulation of the rural world and migration processes, Transition, emblematization and festivalization processes. I argue that the changes of the food consumption in the Entroido gives legibility to the historical and social changes. Although significant changes are detectable, these are not identical in all the Entroidos, due to the specificity of local agents: associations, local authorities and tourist entities. Top-down processes, encouraging festivalization, co-exist with bottom-up processes, and local initiatives for those from inside do not exclude others, produced from the inside out.